2019
DOI: 10.1158/0008-5472.can-19-1147
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Induced Metastasis: Molecular Mechanisms, Clinical Manifestations, Therapeutic Interventions

Abstract: Chemotherapy offers long-term clinical benefits to many patients with advanced cancer. However, recent evidence has linked the cytotoxic effects of chemotherapy with the de novo elicitation of a prometastatic tumor microenvironment. This "modified" tumor microenvironment is triggered by a chemotherapy-driven cytokine storm or through direct effects of certain chemotherapeutics on stromal and/or immune cells, the most critical being tumor-associated macrophages. These chemotherapy-educated cells act as facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 147 publications
(222 reference statements)
3
68
0
1
Order By: Relevance
“…Tumor-associated macrophages (TAMs) with involvement in cancer cell dissemination and metastasis have been previously described in both the primary tumor microenvironment whereby they participate in TMEM assembly and function, and secondary tumor microenvironments (i.e., lungs), whereby they develop metastasis-supporting niches (2,3,8,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). The lymph node microenvironment in this context is rather unique, as it includes at minimum five distinct macrophage subtypes with specific lineage markers and unique immune functions (41,42).…”
Section: Resultsmentioning
confidence: 99%
“…Tumor-associated macrophages (TAMs) with involvement in cancer cell dissemination and metastasis have been previously described in both the primary tumor microenvironment whereby they participate in TMEM assembly and function, and secondary tumor microenvironments (i.e., lungs), whereby they develop metastasis-supporting niches (2,3,8,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). The lymph node microenvironment in this context is rather unique, as it includes at minimum five distinct macrophage subtypes with specific lineage markers and unique immune functions (41,42).…”
Section: Resultsmentioning
confidence: 99%
“…Such racial disparities may partially be due to differences in the TME between AA and EA patients, including the increased density of prometastatic TAMs and microvascular density in black compared to white patients ( 54 , 55 ). Since the main cause of breast cancer morbidity is metastatic disease, in addition to shrinking tumors with cytotoxic and anti-angiogenic therapies, targeting the sites of hematogenous dissemination at TMEM doorways may modify the TME and improve overall survival ( 115 , 119 , 120 ). Since AA compared to EA patients have higher microvascular and macrophage density as explained above, they may also have higher density of TMEM doorways, and thus respond better to anti-angiogenic and anti-TMEM therapy.…”
Section: Can Racial/ethnic Disparities In Breast Tme Help Personalizementioning
confidence: 99%
“…Recent findings in pre-clinical models of cancer have indicated that TAMs also contribute to enhance the metastatic spreading of cancer cells in response to taxanes and anthracyclines [90,197]. Two studies have shown that both classes of cytotoxic agents increased numbers of perivascular, M2-like TIE2 + TAMs in mouse mammary tumours and human breast cancers, which was associated with heightened cancer-cell intravasation and metastatic dissemination in experimental models [198,199].…”
Section: Cytotoxic Chemotherapymentioning
confidence: 99%
“…T Beltraminelli and M De Palma involving upregulation of CCL2, recruitment of CCR2 + monocytes, and facilitation of cancer cell colonization of the lung [41]. Together, the aforementioned studies suggest that, under the influence of chemotherapeutics broadly employed in neoadjuvant (pre-operative) breast cancer therapy, myelomonocytic cells may acquire prometastatic capabilities both in primary tumours and at sites of metastatic dissemination [41,[197][198][199].…”
mentioning
confidence: 97%